Urban Areas in the Perspective of Poverty, Slums, and Urban Heat Island (A Literature Review) - Lasaiba, Mohammad Amin; Lasaiba, Irvan (GEOFORUM, 2022)
The rapid growth of cities, coupled with increasing urbanization, has led to numerous problems. This study employs a literature review method based on critical analysis and in-depth knowledge of relevant literature. The findings of this study indicate that cities in Indonesia are still plagued by poverty, with various social issues creating opportunities for criminal activities, violations of moral norms, irregular land use, and other social phenomena. Additionally, the expansion of slum settlements has further deteriorated the quality of life, contributing to environmental degradation. The urban heat island effect, driven by population growth, the increase in concrete infrastructure development, excessive energy use, and the widespread use of transportation, also exacerbates these issues.